2014
DOI: 10.4161/epi.27696
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling mediated by the FOXA1/A2 transcription factors activatesCFTRexpression in intestinal epithelial cells

Abstract: The forkhead box A transcription factors, FOXA1 and FOXA2, function as pioneer factors to open condensed chromatin and facilitate binding of other proteins. We showed previously that these factors are key components of a transcriptional network that drives enhancer function at the cystic fibrosis transmembrane conductance regulator (CFTR) locus in intestinal epithelial cells. The CFTR promoter apparently lacks tissue-specific regulatory elements and expression of the gene is controlled by multiple cis-acting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…FOXA2 has been described as a transcriptional activator for AFP and albumin (ALB) and regulator of lipid metabolism and fibrinogens [2527]. Furthermore, FOXA2 is involved in development of endodermal-derived organs like the liver, pancreas and lungs [28, 29].…”
Section: Resultsmentioning
confidence: 99%
“…FOXA2 has been described as a transcriptional activator for AFP and albumin (ALB) and regulator of lipid metabolism and fibrinogens [2527]. Furthermore, FOXA2 is involved in development of endodermal-derived organs like the liver, pancreas and lungs [28, 29].…”
Section: Resultsmentioning
confidence: 99%
“…The SNP in the 7p15.2 region most highly associated with prostate cancer risk (rs10486567) is within a motif for AR-FOXA1 and NKX3.1; these factors have been shown to bind to this region in LNCaP prostate cancer cells (Tan et al, 2012). FOXA1 is a pioneer factor that can localize to nucleosome-bound chromatin and serve as a repressor (Bernardo et al, 2013; Lupien et al, 2008); previous studies have shown that FOXA1 is a critical component of a long-range loop (Kerschner et al, 2014). Thus, one possible mechanism by which the 7p15.2 risk region could mediate long-range repression is via formation of a FOXA1-mediated repressive loop.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin structures that facilitate long-range interactions between various regulatory elements cluster specifically to the CFTR promoter exclusively in CFTR expressing cells [25,26]. Recently, it was reported that trans-interacting Forkhead Box A (FOXA) factors induce CFTR activation through binding to a key CFTR cis-regulatory element located in introns 10 and 11 [27][28][29]. CFTR expression is post-transcriptionally regulated also by miRNAs, such as miR-145 and miR-494 [30][31][32].…”
Section: Introductionmentioning
confidence: 99%